Diastratic variations in the discursive praxis of cusquenian spanish - Rojas Anaya, Yanina (2021)
The analysis of diastratic variations in natural situations is fundamental due to its contribution to the sciences of language, since in this way the form of expression that exists in different contexts can be identified. Direct observation and the interview used in this research show peculiar characteristics of Cusco Spanish in discursive praxis, in which the alternation of codes is verified due to the influence of a language A in a language B, which gives it some significant differences, seen from dialectology and sociolinguistics. These variations are presented from the sample selected for convenience, in which the contributions of 70 subjects, between men and women, from urban and rural areas, all of them with a level of knowledge of the spoken language, were considered.